Determinan Minat Beli KPR Generasi Urban Milenial DI Kota Bandung - Muhamad Wahyu Hamijaya; Restu Akbar Suryaman (Jurnal Riset Ilmu Ekonomi, 2023)
In recent years, banks in Indonesia have been competing to attract interest in buying mortgages for the millennial segment. The pattern of approach taken by banks is through competition for down payments, interest rates, credit ceilings, to the ease of applying for credit. This study aims to analyze product attributes, marketing communications, location and their influence on the intention to buy housing for millennials. The method used in this research is descriptive and verification. In order to obtain relevant results, this research is based on primary data from 400 respondents. The results of the analysis show that product attributes have a more dominant role compared to other variables. Meanwhile, marketing communications have very little effect on the interest in buying housing for millennials. Regarding the location aspect, in general the millennial generation sees quite well the location aspect in forming interest in mortgage financing schemes for millennials, and the millennial generation's buying interest is mostly based on personal references, this is evidenced by the average score regarding transactional and preferential interest higher than the indicators of referential and explorative interest.